Membangun Ekosistem E-Commerce yang Berkelanjutan untuk Industri Kreatif : Tantangan dan Peluang bagi Pemerintah - Fitria Marisya; Wahyudi Syaputra; Sri Dweni Astuti; Jamilah Jamilah (Universitas 17 Agustus 1945 Semarang, 2025)
This research examines crucial issues related to the development of a sustainable e-commerce ecosystem for the creative industry in Indonesia. The main problems identified are uneven digital infrastructure, lack of digital literacy, and fierce competition in local and global markets. The purpose of this study is to analyze the challenges and opportunities faced by creative industry players in utilizing e-commerce platforms. The method used is literature review by collecting data from various secondary sources, including journal articles and policy reports. The results of the study show that collaboration between the government, the private sector, and local communities, as well as effective training programs, are very important to improve the competitiveness of creative industry players. The conclusion of this study emphasizes the need for an integrated approach in creating an e-commerce ecosystem that supports the growth of the creative industry in the digital era.